Developing and applying a constitutional framework for public participation in South Africa - Burnell, Matthew Grant (Department of Public Law, 2018)
Online public participation platforms have resuscitated the debate globally about whether the Internet can be used to improve the reach of public participation and the quality of comments received during these processes or not. This thesis highlights that this debate is a ruse. Our focus should not be on the mode of participation adopted to engage with interested and affected parties but rather on the manner in which that mode (whether online platforms or more traditional methods) is implemented. Currently in South Africa there is not a standard set of guidelines to assist persons undertaking these modes of participation to ensure that they are adequate or acceptable. This thesis seeks to create such a framework. As all actions in South Africa must comply with the Constitution, it is the starting point for developing this baseline. The Constitution drafters introduced participatory democracy into the South African legal framework. In doing so, they intended that certain principles associated with this notion filter into the legal system. This thesis identifies these principles, drawn from the works of democratic theorists, Constitutional-era South African case law, legislation, practice and administrative process, and proposes a participatory framework ('the Constitutional Framework for Public Participation' or 'CFPP') which, if followed, will ensure that policymaking and administrative participatory processes comply with the Constitutional conception of participatory democracy. In addition, as online participation is most likely to become a prominent tool in engaging interested and affected parties, this thesis considers whether there are any principles relating specifically to online participation which should be included in the CFPP. Following an assessment of online public participation processes, additional principles have been identified but these principles apply equally to offline modes of participation as to online participation. Having incorporated these additional principles into the CFPP, they are applied to the public participation process required in terms of Environmental Impact Assessment ('EIA') to assess whether these processes are being conducted in a Constitutional manner. The findings reveal that the regulations governing the EIA public participation processes fall short of the CFPP. Although the regulations are inadequate, examples of actual EIA public participation processes are examined to determine whether, notwithstanding the inadequate regulations, the implemented public participation process meet the requirements of the CFPP. This also yields a negative outcome, highlighting that public participation processes are not being conducted in a manner required by the Constitution. This thesis suggests that the CFPP can be consulted to assist lawyers, administrators, legislatures, persons responsible for public participation processes, government and others in designing and implementing constitutionally acceptable public participation processes. It is acknowledged that the CFPP will need to be the subject of empirical investigation by subsequent researchers to assess its effectiveness in achieving this objective.